A 'Holding Place': An Indigenous Typology to Mediate Hospital Care. Issue 1 (2nd January 2022) - McGaw, Janet; Vance, Alasdair; Patten, Uncle Herb
Abstract : Indigenous people in Australia suffer from significant disparities in health compared to their non-Indigenous peers. Policies to address it have had little success. Using Michel Foucault's concept of 'enunciative modalities' and Wiradjuri historian Lawrence Bamblett's theory of deficit discourses and 'straightline stories, ' which builds on Foucauldian theory, this essay explores the reasons for the failures, the complicity of architecture, and responses by the discipline. This article (coauthored with an Aboriginal doctor and academic, and an Elder in the community) argues hospitals, in particular, are alienating environments. It proposes a new Indigenous-led typology to mediate hospital care that is spatio-temporally and materially different.